24. OUTCOMES OF CONGENITAL HEART DEFECT TREATMENT USING INTERVENTIONAL CARDIOLOGY AT CHILDREN'S HOSPITAL 2 FROM 2018 TO 2023 (Vietnam Journal of Community Medicine, 2025)
Objectives: A study on the characteristics and outcomes of transcatheter interventions in children with congenital heart defects at Children's Hospital 2 from 2018 to 2023.Methods: A retrospective cross-sectional descriptive study was conducted based on medical records of inpatient CHD cases over a 6-year period. Epidemiological indicators, types of CHD, interventions, and treatment outcomes were analyzed by year.Results: From January 2018 to December 2023, we performed catheter-based interventions on 2,667,000 cases of congenital heart disease. Of these, 18.4% were admitted through the emergency department. The mean age was 14.5 ± 24.3 months. Congenital heart defects with left-to-right shunts accounted for the highest proportion (53.6%). Temporary transcatheter interventions represented 34.1% of total cases, with ductal stenting being the most common procedure (69%). The overall success rate of interventional procedures in our study was 93.7%. Age and weight were identified as two significant factors associated with the risk of complications.Conclusions: Transcatheter intervention is a safe and effective treatment method for various types of congenital heart defects, particularly simple lesions such as patent ductus arteriosus, atrial septal defect, and pulmonary valve stenosis. Despite technical challenges in younger and lower-weight patients, treatment outcomes have significantly improved over time thanks to accumulated experience and advancements in technique.
Keywords: Congenital heart diseases, disease model, Children’s Hospital 2